Is The Size of the Currently Available Implants for Total Hip Arthroplasty Adequate for Our Population? - Busato, Thiago Sampaio; Barbosa, Gabriella Maira Rodrigues; Velho, Anderson Emanuel Kumandala; Matioski Filho, Gladyston Roberto; Godoi, Lucas Dias; Capriotti, Juan R.V. (Revista Brasileira de Ortopedia, 2019)
Objective To determine if the dimensions of selected national and imported implants used in total hip arthroplasty surgeries are adequate regarding the anthropometric profile of the Brazilian population.Methods A retrospective study of patients submitted to primary total hip arthroplasty. Patients with femoral or acetabular morphological deformities that could influence the choice of implant size, including dysplasia and previous fractures, were excluded from the study. Two national implants and six imported implants were included in the study. Every patient was treated by the same group, with one of the four senior authors or under their strict supervision, following the same surgical technique. The data were analyzed regarding gender, age, fixation type and implant model.Results The analysis of 682 hips submitted to total hip arthroplasty demonstrated that 2 models of cemented femoral stems and 1 of non-cemented stem did not seem to be perfectly adequate for the femoral morphology of the studied population, since these 3 implants were mostly used in the smallest size available, resulting in a non-Gaussian curve. The mean diameter of the native acetabulum was 54 mm in men and 52 mm in women.Conclusion Out of the eight models studied, five were deemed adequate for the studied population. The other three models available in our market (two national models and one imported model) apparently require more appropriate sizing. We emphasize that anthropometric studies of the Brazilian hip are necessary to give scientific subsidies to the ideal implant design for our market.
Keywords: arthroplasty, replacement, hip; hip fractures; hip prosthesis; prosthesis design